(untitled) (Prithvi Academic Journal, 2026)
Forest, agricultural lands and wetlands in the low lands Terai belt of Nepal are vulnerable to infestation by invasive alien plant species (IAPS). The study area is characterized by a typical tropical climate and is located in the lowland of the country, making it suitable for biological invasion. The forest in this area is found dominated by Shorea robusta. The survey research aimed to assess the invasiveness of IAPS along the roadsides adjacent to agricultural land in Banke district. Five sites Dhakeri, Khajura, Chisapani, Narainapur and Nepalgunj areas were selected as sampling sites. The sampling plots of 10m×10m were randomly established at each sites to measure the invasiveness of IAPS. The study revealed total 84 plant species, of which 20 species were identified as non-invasive naturalized and 16 species as invasive plants. Among 16 IAPS, Ageratum houstonianum was noticed as the most invaded, followed by Ipomoea carnea, Parthenium hysterophorus. Among five sampling areas, Nepalgunj area was observed as the most problematic area followed by Dhakeri and Chisapani areas. The impacts of IAPS were noticed in richness of native herb species due to suppressing of their growth and regeneration.